[1–7-NαC]-Crocaorb A1 and A2, orbitides from the latex of Croton campanulatus - Queiroz, Suzana A.S. [UNESP]; dos Santos, Ana Letícia P. [UNESP]; Bobey, Antonio F. [UNESP]; Cabral, Vinicius A.; Verli, Hugo; dos Santos Magalhães, Tatiana B.; Guimarães, Elisalva T.; Soares, Milena B.P.; Aguiar, Anna Caroline C.; Guido, Rafael V.C.; Trovó, Marcelo; Cilli, Eduardo M. [UNESP]; et al. (Elsevier, 2024)
Two new heptapeptides, [1–7-NαC]-crocaorbs A1 (1) and A2 (2), were isolated from the latex of Croton campanulatus. Their structures were determined using NMR spectroscopic techniques, ESI-HRMS data, Marfey's method, and further refined using molecular dynamics with simulated annealing (MD/SA). Molecular dynamics calculations of peptides 1 and 2 demonstrated greater stability in simulations using a biological solvent compared to those using DMSO. Compound 1, the most abundant peptide in latex, was assessed for NO production, antiplasmodial and cytotoxicity activities. The peptide significantly increased nitric oxide (NO) production at concentrations of 40, 20 or 10 μM (17.932 ± 1.1, 18.270 ± 0.9, 18.499 ± 0.7, respectively). Its antiplasmodial activity exhibited limited efficacy, with only 5% inhibition of Plasmodium falciparum 3D7 growth at a concentration of 50 μM. Also, it exhibited no cytotoxic effects in the J774A.1 murine macrophages cell line. This study represents the first report of a phytochemical investigation of the species C. campanulatus, which showed orbitides with distinctive sequences in contrast to other peptides described for the genus Croton and contributes to the study of structural diversity within this particular class of compounds.
Keywords: Croton campanulatus Caruzo & Cordeiro; Cyclic peptides; Euphorbiaceae; Orbitides